1998
DOI: 10.1089/clm.1998.16.123
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Laser Disc Decompression in Spinal Stenosis

Abstract: It was our conclusion that PLDD compares favorably with open surgery in the treatment of lumbar spinal stenosis that is partially or completely due to bulging or protruding discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…These criteria excluded patients previously operated upon, patients with even first-degree spondylolisthesis, moderate osteoarthritis, scoliosis, and spinal stenosis. As more experience was gained worldwide, all of these "contraindications," including spinal stenosis, 10 have been discarded, and PLDD has been found to be effective in these conditions. Until now, extruded, nonsequestered discs were still considered a contraindication to PLDD.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria excluded patients previously operated upon, patients with even first-degree spondylolisthesis, moderate osteoarthritis, scoliosis, and spinal stenosis. As more experience was gained worldwide, all of these "contraindications," including spinal stenosis, 10 have been discarded, and PLDD has been found to be effective in these conditions. Until now, extruded, nonsequestered discs were still considered a contraindication to PLDD.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 84 studies identified, 67 were excluded. Table 6 shows the reasons for exclusion of selected articles (35,46,145,146,149,(151)(152)(153)(154)(155)(157)(158)(159)(161)(162)(163)165,167,169,171,172,(174)(175)(176)(179)(180)(181)(182)(183)(184)(185)(186)(187)(189)(190)(191)(192)(193)195,196,(202)(203)(204)(205)(206)208,210,212,216,…”
Section: Limited or Poormentioning
confidence: 99%
“…Since then, the development of laser therapy for spinal diseases has focused on lumbar disc disease, and PLDD became an active treatment following FDA approval in 1991 5) . Also, its application range has been expanding in recent times to include treatment of lumbar spinal stenosis and endoscopic treatment of ruptured cervical disc 8,9) . This report aims to introduce the different methods of laser treatment and their effects on surgical treatment of spinal diseases.…”
Section: Introductionmentioning
confidence: 99%